2010
DOI: 10.1177/0022427810375574
|View full text |Cite
|
Sign up to set email alerts
|

Betwixt and Between: The Role of Psychosocial Factors in the Early Stages of Desistance

Abstract: This article presents the results of an investigation into the psychosocial changes involved in the early stages of desistance, which to date have attracted little empirical or theoretical attention. The study used a mixed-methods design to produce a nuanced account of the shifts that occur in cognitions and social circumstances as offenders make the transition to desistance. Three psychometric instruments were completed by 73 adult males aged 18 to 35 who had acquired at least two previous convictions and wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Secondly, and more fundamentally, focusing heavily on events such as marriage places the primary emphasis on the actions of the change agent (what spouses do, what the marital bond offers). This contrasts with a view of desistance that incorporates to a greater extent the actor’s own subjective changes and associated agentic moves, which are theorized as an essential aspect of the change process (Giordano et al, 2002; Haigh, 2009; Healy, 2010; Maruna, 2001). This cognitive emphasis provides a more conditional perspective on change, and on the prosocial impact of specific change agents.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Secondly, and more fundamentally, focusing heavily on events such as marriage places the primary emphasis on the actions of the change agent (what spouses do, what the marital bond offers). This contrasts with a view of desistance that incorporates to a greater extent the actor’s own subjective changes and associated agentic moves, which are theorized as an essential aspect of the change process (Giordano et al, 2002; Haigh, 2009; Healy, 2010; Maruna, 2001). This cognitive emphasis provides a more conditional perspective on change, and on the prosocial impact of specific change agents.…”
Section: Introductionmentioning
confidence: 90%
“…While this cognitive transformation is generally considered necessary for breaking habits (see especially Healy, 2010) and discarding old lifestyles, we have also emphasized that specific “hooks” for change play an important role in allowing the individual to craft a satisfying and achievable replacement self (Giordano et al, 2002). Further, such hooks undoubtedly vary in their transformative potential.…”
Section: Introductionmentioning
confidence: 99%
“…Desistance studies examine the socio-economic conditions, psychological factors, and therapeutic programmes that can contribute to an individual's decision to stop breaking the law (Giordano, Cernkovich and Rudolph 2002;Laub and Sampson 2001). Research has suggested that a wide range of variables is associated with desistance, including marital status, employment, community supervision programmes, and age (for example, Bersani, Laub and Nieuwbeerta 2009;Craig and Foster 2012;Farrall et al 2011;Forrest and Hay 2011;Healy 2010Healy , 2012 and that desistance patterns vary by gender (Brown and Ross 2010;Giordano, Cernkovich and Rudolph 2002;Herrschaft et al 2009;Opsal 2012;Rumgay 2004).…”
Section: Desistance Identity and Prisonmentioning
confidence: 99%
“…A higher pro‐offending attitudes score denotes a higher favorable attitude toward offending, whereas a higher self‐perceived life problems score indicates that participants have life problems in many areas. Sample items of pro‐offending attitudes include, “In the end, crime does pay,” “Committing crime is quite exciting,” and, “I always seem to give in to temptation,” whereas sample items of self‐perceived life problems include, “Problems with relationships,” “Controlling temper,” and, “Lots of worries.” Overall, the CRIME‐PICS II has been reported to be a valid and reliable measure in recent studies, with moderate to high internal consistency (ranging from 0.55 to 0.83; Frude et al, ; Healy, ; Wood, Kade, & Sidhu, ). Similarly, the CRIME‐PICS II was found to be high in internal consistency (Cronbach's α = 0.79).…”
Section: Methodsmentioning
confidence: 99%